2005
DOI: 10.1111/j.1365-2249.2005.02765.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B surface antigen presentation and HLA-DRB1*– lessons from twins and peptide binding studies

Abstract: SummaryThe aim of this study was to investigate the underlying mechanisms of the genetic association between certain HLA-DRB1* alleles and the immune response to HBsAg vaccination. Therefore, HBsAg peptide binding to HLA-DR molecules was measured in vitro by peptide binding ELISAs. Additionally, HBsAg-specific T cell reaction and cytokine profile of immune response were analysed ex vivo in ELISPOT assays and DR-restriction of T-cell proliferative responses was investigated with HBsAg specific T cell clones. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Immune responses induced by vaccination are in part under genetic control, and the degree of heritability varies by vaccine between 35 and 90%, as shown by family and twin studies both within African settings Marchant et al 2006;Newport et al 2004bNewport et al , 2005 and across the rest of the world (Alper 1995;De et al 2001;Hohler et al 2002;Konradsen et al 1993Konradsen et al , 1994Kruger et al 2005;Lin et al 1989;Musher et al 2000, Musher et al 1997 and reviewed by Kimman et al 2007). Additionally, we know that diVerences in vaccine eYcacy exist between diVerent ethnic groups, also indicating a putative role for genetic factors (Kimman et al 2007).…”
Section: Vaccine-induced Immunitymentioning
confidence: 94%
“…Immune responses induced by vaccination are in part under genetic control, and the degree of heritability varies by vaccine between 35 and 90%, as shown by family and twin studies both within African settings Marchant et al 2006;Newport et al 2004bNewport et al , 2005 and across the rest of the world (Alper 1995;De et al 2001;Hohler et al 2002;Konradsen et al 1993Konradsen et al , 1994Kruger et al 2005;Lin et al 1989;Musher et al 2000, Musher et al 1997 and reviewed by Kimman et al 2007). Additionally, we know that diVerences in vaccine eYcacy exist between diVerent ethnic groups, also indicating a putative role for genetic factors (Kimman et al 2007).…”
Section: Vaccine-induced Immunitymentioning
confidence: 94%
“…Model-fitting analyses were done to dissect genetic and environmental components of vaccine responses, revealing that the HLA-DRB1* alleles 01, 11 and 25 were associated with good HbsAg vaccine responses. Further studies by this group suggested that differences in the T cell recognition of peptide/MHC complexes are a critical event in T cell responsiveness to HBsAg [16]. The heritability of the HBsAg vaccine response accounted for by the HLA-DRB1* locus was subsequently estimated to be 25% (as estimated by comparison of intraclass correlations of dizygotic twin pairs who had an identical genotype at the HLA-DRB1* locus with those of dizygotic twin pairs who had a different genotype), leaving the remaining heritability of 36% to other gene loci.…”
Section: Individual Differences In the Response To Vaccination: Twin mentioning
confidence: 99%
“…These differences have been explored experimentally in detail. Multiple groups have found that antigen-presenting cells (APCs) from peripheral blood mononuclear cells of non-responders are able to stimulate DR-matched helper T cells from responders as effectively as APCs from high responding individuals making a deficit in antigen processing and presentation less likely [25,[73][74][75]. Conversely, these studies found that the T-cells from non-responders could not be activated by either their non-responding APC counterpart or DR-matched APCs from responders.…”
Section: (D) Origins Of Study Heterogeneitymentioning
confidence: 99%